Study the Effect of 12-Hydroxyoctadecanoic Acid Concentration on Preparation and Characterization of Floating Organogels using Cinnarizin as Modeling Drug - Masar Basim Mohsin Mohamed; Zainab Saad Qaddoori; Ghiadaa Sulaiman Hammed (College of Pharmacy University of Baghdad, 2022)
This work targeted studying organogel as a potential floating system. Organgel has an excellent viscoelastic properties, floating system posses a depot property.  Different formulations of 12-hydroxyoctadecanoic acid (HOA) in sesame oil were gelled and selecting F1, F3 and F5 HOA organogels for various examinations: tabletop rheology, optical microscopy, and oscillatory rheology studies. Also, the floating properties studies were conducted at in vitro and in-vivo levels. Lastly, the in-vitro release study using cinnarizine (CN) was to investigate the organogel depot property. Based on the results, the selected concentrations of HOA in sesame oil organogels showed temperature transitions from gel to sol higher than body temperature. These organogels scaffolds inner structures were a star-like shape. The formulation F5 HOA/SO organogels were developing higher storage modulus values, which resulted from the amplitude sweep study. Indeed, all the selected organogels were frequency sweep independent. The organogel's in vitro floating properties were found positively proven our work's aim and were buoyant for 24 hours as F5 HOA organogels remained for 12 hours in the rat's stomach. The depot property showed the slow release of CN from F5 HOA/SO organogel and not more than 65% w/w of CN released after 24 hours.